DTA measurements in the ternary Ag-Au-Ga system - Jendrzejczyk-Handzlik D.; Handzlik P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this work, the ternary Ag-Au-Ga system was studied experimentally by differential thermal analysis (DTA). The measurements were carried out along two chosen cross-sections determined by the ratio of mole fractions XAg/XGa=1:1 and XAu/XGa=1:1 by applying Pegasus 404 apparatus form Netzsch. The experiments were performed at three rates: 1 K min-1, 5 K min-1, and 10 K min-1. Next, the obtained experimental results were used to estimate the temperatures of liquidus by applying extrapolation to a zero rate. Moreover, the temperatures of invariant reactions and other phase transformations were investigated from DTA measurements which were carried out with the rate 1 K min-1. Finally, the experimental results were compared with the isopleths obtained from the prediction and calculation of the phase diagram which were done by using CALPHAD method. The experimental data obtained in this work are in good agreement with the calculation results.